The Role of Arabic Lexicons in Teaching Ta’bîr Material at the Islamic Boarding School for Girls - Marlina, Lina; Farraj, Khalid Khamis; Zahra, Maryam Jamilah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This research highlights the importance of the Arabic lexicon in teaching and studying ta’bîr courses in Ma’had al-Imarat Bandung. This qualitative research depends on a field study and a descriptive analysis. This importance is due to three aspects: The first is the ta’bîr courses of materials prescribed in any Arabic language learning institutes to develop students’ four skills. The second is that lexicons are tools for teaching and learning the Arabic language, especially in the subject matter of ta’bîr. The third is that the Arabic lexicon is one of the primary sources people refer to correct their linguistic knowledge. The results indicate that language acquisition is the most important of that knowledge. Furthermore, in acquiring the Arabic language, many factors are linguistic and non-linguistic. Dictionaries are considered one of the primary tools in language acquisition in studying the subject matter of ta’bîr.